COMBINATION OF SOYBEAN MEAL AND Hibiscus tiliaceus LEAF IN THE GOAT DIET: EFFECT ON SOME PARAMETERS OF PROTEIN METABOLISM - Akhsan, F.; Nuswantara, L. K.; Achmadi, J. (Journal of the Indonesian Tropical Animal Agriculture, 2015)
Sixteen Ettawah cross bred goats were used to study the effect of waru leaf (Hibiscus tiliaceus)sapponin combined with soybean meal protein supplementation on some parameters of proteinmetabolism. Goats had body weight average of 16 kg and aged at 7 months. The experimental dietswere: T0 = total mixed ration (0.9% saponin of hibiscus leaf, 8% CP, 62% TDN), T1 = T0 + 3% soybeanmeal protein, T2 = T0 + 6% soybean meal protein, and T3 = T0 + 9% soybean meal protein. Thetreatments were allocated in a completely randomized design. The parameters observed in this studywere dry matter (DM) and crude protein (CP) intakes, DM and CP digestibilities, ruminal amonia andVFAs concentrations, blood urea level, nitrogen retention, digestible organic matter in rumen (DOMR),urinary allantoin, and estimated microbial nitrogen (N) synthesis. DM intake, DOMR, urinary allantoinand estimated microbial N synthesis were not affected significantly (P>0.05) by treatments. CP intake,DM and CP digestibilities, ruminal amonia and VFAs concentrations, blood urea level and nitrogenretention increased (P<0.05) with increasing levels of soybean meal protein. Balancing energy levelshould be considered for the dietary protein supplementation in Hibiscus tiliaceus leaf contained diet of goat.